Potential of Cassava Peel as an Alternative Growth Media of Aspergillus niger and Rhizopus oryzae with Concentration Modification - Artati Artati; Risky Risky; Rafika Rafika; Zulfian Armah; Syahida Djasang; Asriyani Ridwan; Aan Yulianingsih Anwar (Jurnal Media Analis Kesehatan, 2023)
Waste is the waste product of a production process or materials that are no longer valuable or worthless, including waste from food processing processes. One of the main food wastes produced in developing countries is cassava peel from a plant with the Latin name Manihot ultisima. Cassava skin is the outer layer of the tuber which functions as a protector for the cassava flesh. This research aims to prove that cassava peel can be used as raw material for making alternative media for fungal growth and to find out the most effective concentration to use. This research is experimental using cassava skin as a sample. In this research, data analysis was carried out using the One-Way Anova Test. Concentrations of 5%, 10%, 15%, 20%, 25% and 30% were made as alternative media for the growth of Aspergillus niger and Rhizopus oryzae fungi and SDA media as a control. During the incubation period for these two species, both Aspergillus niger and Rhizopus oryzae experienced growth which became bigger day by day. The conclusion of this research is that cassava peel can be used as a natural ingredient that can be used as an alternative medium for fungal growth. In the alternative media for cassava peel, the most effective concentration of the Aspergillus niger species is 20%, while for the Rhizopus oryzae species it is 15%